Teaching grammar through song-based activities - Zeman, Martin (Univerzita Pardubice, 2017)
The bachelor thesis deals with creating song-based activities for the students of the stage 2 of the elementary education. The activities are aimed at teaching grammar with special attention directed to explaining and practicing the difference between the present perfect simple and past simple. The theoretical part defines the key concepts and terms needed for the practical part, including the communicative competence, the framework education program for elementary education, the present perfect simple together with the past simple, using songs as authentic materials to teach grammar and lesson planning. The practical part is focused on individual activities that are constructed and inspected based on the outcomes of the theoretical part.
Teaching grammar through song-based activities
Keywords: komunikační kompetence; rámcový vzdělávací program pro základní vzdělávání; předpřítomný čas prostý; minulý čas prostý; písně; gramatika; plánování lekcí; communicative competence; framework education program for elementary education; present perfect simple; past simple; songs; grammar; lesson planning